Теоретичні аспекти інфраструктурного забезпечення товарних потоків підприємств - Акімова, Е. Ш. (Ways to Improve Construction Efficiency, 2013)
Theoretical approaches to interpret the notion of enterprise infrastructure is considered in the article. Held structuring and filling the functional content of the concept of "infrastructural support of goods flow" on the enterprise in order to further evaluate it in practice.